A Few Remarks on the Ransom Paid for Releasing Captives in Selected Early Byzantine Hagiographic Texts - Milewski, Ireneusz (Studia Ceranea, 2017)
The article analyzes certain early Byzantine hagiographic texts concerning various forms of brigandage (both maritime and land-based). Two such accounts are studied in detail, one by Gerontius of Jerusalem and another by Theodoret of Cyrus. The instances described unveil the weakness of Roman state structures at the borders of the state as well as in lands harassed by barbarian raids, including piracy. Despite certain flaws (mostly the lack of precision), the accounts under discussion constitute valuable and reliable sources of historical knowledge.